Urban Policy Analysis in Street Vendor Arrangement on Padang Beach - Purnomo, Dwi; Yusran, Rahmadani (Department of Government Studies, Universitas Syiah Kuala, 2024)
This research aims to identify the ways in which the urban regulations of Padang Beach have affected the ways in which street sellers do business. The author carried out this study by employing descriptive qualitative methods. Interviews and documentation are the means of data collection employed in this study. After completing the data reduction, data presentation, and conclusion drawing steps of the data analysis process, conclusions were drawn. This study draws on Blackman's theory of urban policy, which focusses on public service provision and access improvement in metropolitan areas. According to the study's findings, both enabling and limiting variables impact the implementation of street vendor arrangements from an urban policy standpoint. The problems faced in structuring street vendors are regulations and institutions, availability of land for developing facilities, empowerment and supervision and partnerships and the role of the community. So, to fix issues with street vendor management in the Padang Beach region, we need a more holistic and coordinated approach.